HARMONIZATION OF ACCOUNTING, ANALYSIS AND AUDIT OF FOREIGN ECONOMIC OPERATIONS IN THE CONTEXT OF IMPLEMENTATION OF REGULATORY STANDARDS OF THE EU - Myskin, Yurii; Savchenko, Alla; Kolisnyk, Olena (Український економічний часопис, 2025)
The article examines the theoretical and methodological aspects of the harmonization of accounting, analysis and auditing of foreign economic operations in the context of the implementation of EU regulatory standards. Key aspects of the implementation of Directive 2013/34/EU, Regulation (EU) No. 537/2014 and BEPS principles, their impact on financial reporting, audit and tax control of foreign economic activities of enterprises are considered. Special attention is paid to the concept of integrated accounting and analytical support for management decisions, which is based on the synergy of financial, managerial and strategic analysis, using modern ERP systems for process automation. A theoretical model of integrated security is proposed, which allows to increase the transparency of financial information, the effectiveness of risk management and the investment attractiveness of enterprises in the international environment. Practical recommendations on the adaptation of national accounting standards to international requirements, improvement of audit procedures and the use of innovative analytical tools have been developed. The results of the study are aimed at improving the accounting and analytical support of foreign trade in the conditions of European integration and global challenges of the economy.